Imaging of High-Speed Aerial Targets With ISAR Installed on a Moving Vessel - Dau-Ming Wu; Jean-Fu Kiang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2023)
An inverse synthetic aperture radar (ISAR) technique is proposed to acquire high-resolution steady images of high-speed aerial target with radar installed on a moving vessel. The phase changes due to target motion and attitude perturbation of the vessel are compensated. A 2-D ISAR imaging method is enhanced to acquire 3-D-compatible images of uncooperative targets. The target motion parameters are fine-tuned iteratively to better focus the target image. A $(ζ _{h}, ζ _{v})$ plane is proposed to display 3-D targets for visual-like perception. The 2-D ISAR images, thus, focused on the preserve features of the original 3-D targets, including shape and size. Imaging of several aerial targets is simulated to demonstrate the efficacy of the proposed approach.